FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JAGUNG DI DESA KIRITANA KECAMATAN KAMBERA KABUPATEN SUMBA TIMUR - Anggreni Madik Linda (Universitas Galuh Ciamis, 2020)
This study aims to determine the factors that influence corn production in Kiritana Village, Kambera District, East Sumba Regency. This research was conducted in January 2020. The method of taking respondents using simple random sampling of 30 farmer respondents. This research uses descriptive quantitative method. The results of this study indicate that the variable land area (X1), seeds (X2), the number of labor (X3) and the use of herbicides (X4) simultaneously have a significant effect on corn production. Partially, the variable land area (X1) and seed (X2) have a significant effect on corn production, while the number of labor (X3) and herbicide use (X4) have no significant effect.